Deep Chandra observation and numerical studies of the nearest cluster cold front in the sky - Werner, N.; ZuHone, J. A.; Zhuravleva, I.; Ichinohe, Y.; Simionescu, A.; Allen, S. W.; Markevitch, M.; Fabian, A. C.; Keshet, U.; Roediger, E.; Ruszkowski, M.; Sanders, J. S. (Monthly notices of the Royal Astronomical Society, 2016)
We present the results of a very deep (500 ks) Chandra observation, along with tailored numerical simulations, of the nearest, best resolved cluster cold front in the sky, which lies 90 kpc (19 arcmin) to the north-west of M 87. The northern part of the front appears the sharpest, with a width smaller than 2.5 kpc (1.5 Coulomb mean free paths; at 99 per cent confidence). Everywhere along the front, the temperature discontinuity is narrower than 4–8 kpc and the metallicity gradient is narrower than 6 kpc, indicating that diffusion, conduction and mixing are suppressed across the interface. Such transport processes can be naturally suppressed by magnetic fields aligned with the cold front. Interestingly, comparison to magnetohydrodynamic simulations indicates that in order to maintain the observed sharp density and temperature discontinuities, conduction must also be suppressed along the magnetic field lines. However, the northwestern part of the cold front is observed to have a non-zero width. While other explanations are possible, the broadening is consistent with the presence of Kelvin–Helmholtz instabilities (KHI) on length-scales of a few kpc. Based on comparison with simulations, the presence of KHI would imply that the effective viscosity of the intracluster medium is suppressed by more than an order of magnitude with respect to the isotropic Spitzer-like temperature dependent viscosity. Underneath the cold front, we observe quasi-linear features that are ∼10 per cent brighter than the surrounding gas and are separated by ∼15 kpc from each other in projection. Comparison to tailored numerical simulations suggests that the observed phenomena may be due to the amplification of magnetic fields by gas sloshing in wide layers below the cold front, where the magnetic pressure reaches ∼5–10 per cent of the thermal pressure, reducing the gas density between the bright features.
Keywords: Hydrodynamics; Instabilities; Galaxies –clusters –individual (Virgo); Galaxies – clusters – intracluster medium; X-rays – galaxies – clusters